La bioseguridad y los servicios de alimentación turística en el cantón Quevedo, 2020 - Barro Vera, Walter Jesus (2021)
The purpose of this project is to present an analysis of biosecurity in quality tourist food services in the canton of Quevedo, through a micro evaluation it was possible to identify the current state of food biosecurity and analyze the current situation of the operation of tourist establishments where shortcomings were detected in the services provided to tourists, thus, proposals arise for the improvement of these and thus provide a better service by applying biosecurity in tourist establishments. A problem that still exists in the canton of Quevedo is that despite having an excellent tourist activity and with the financing of entrepreneurs who have decided to invest in the city for its economic development, it lacks the biosafety of tourist food services to enhance this sector. With the support of the GAD of the canton Quevedo, it will be able to provide quality services and this will influence the tourist, economic and social development of the canton since, with its environmentally friendly infrastructure many tourists will choose this site as an option for vacation and so they can also learn a little more of this city, likewise should be given an excellent service to people so they can feel satisfied and decide to return to the city.